Multi-factor coupled failure mechanism of W–Cu functionally graded material under thermal shock service - Pengqi Chen; Dang Xu; Chengyang Huang; Jian Yang; Yunxiao Tai; Tao Hong; Jigui Cheng; Hongyu Chen (Journal of Materials Research and Technology, 2023)
The stability of W–Cu functionally graded material (FGM) as a heat sink connecting material is of significant importance for long-term service under high-temperature thermal cycling conditions. In this study, W–Cu FGM was successfully fabricated by powder metallurgy method. Various thermal shock experiments were performed on the samples at different temperatures and cycles, and a comprehensive investigation was conducted into its service failure mechanisms. The findings demonstrate that as the temperature increases to 1000 °C, the layer with low copper content gradually developed microcracks, and the microstructure changed from the original uniform distribution to a copper granular exudation, ultimately forming a network-like copper layer. The layer with high copper content undergoes a transition from slight undulations and roughness to the emergence of numerous cracks and pores, accompanied by the formation of a larger area of copper pool structures. After 1000 °C thermal shock for 200 cycles, the thermal conductivity decreases from 215.33 W m−1 K−1 to 168.24 W m−1 K−1, the bending strength decreased from 686.75 MPa to 115.77 MPa at room temperature, with reductions of 22.4 % and 81.2 %, respectively. At this point, the sample severely failed. The study highlights that the thermal shock failure mechanism of the gradient W–Cu samples is a novel multifactor coupled failure mechanism. It is influenced by the combined effects of crack initiation and propagation induced by thermal stress and the evolution of microstructural changes.